1991
DOI: 10.1038/bjc.1991.426
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid dysfunction can predict response to immunotherapy with interleukin-2 and interferon-2α

Abstract: Thyroid dysfunction is a well-recognised side-effect of treatment with interleukin-2 (IL2). We assessed the correlation between the development of abnormal thyroid function and tumour response in 13 patients receiving IL2 and interferon-2 alpha (IFN2 alpha) for advanced malignancy. Seven patients had normal thyroid function during treatment, and all of these patients have since died of progressive disease. Of six patients who did develop thyroid dysfunction during treatment, one patient has died of progressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 11 publications
0
7
1
Order By: Relevance
“…Thyroid dysfunction was not associated with the response of chronic hepatitis C to IFN-a therapy in the present study; in contrast a positive relationship between the appearance of thyroid dysfunction and the response to IFN-a therapy was observed in previous studies (7,34,35). However, all those previous studies did not evaluate the pretreatment serum HCV RNA levels.…”
Section: Discussioncontrasting
confidence: 54%
“…Thyroid dysfunction was not associated with the response of chronic hepatitis C to IFN-a therapy in the present study; in contrast a positive relationship between the appearance of thyroid dysfunction and the response to IFN-a therapy was observed in previous studies (7,34,35). However, all those previous studies did not evaluate the pretreatment serum HCV RNA levels.…”
Section: Discussioncontrasting
confidence: 54%
“…[29][30][31] In our patients, the presence of thyroid dysfunction did not lead to changes in the dose or therapy withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have suggested that patients who develop thyroid autoimmunity in relation to IFN-α treatment, or to combined therapy with interleukin-2 (IL-2) and IFN-α, have a better clinical response of the underlying disease [106,107], but this was not confirmed by other studies [18,41,91,92]. Recently, a correlation between the degree of autoimmune disease and improved prognosis in metastatic renal cancer has been reported, suggesting that autoimmunity while on cytokine therapy may mark a breach of immune tolerance in patients with cancer [108].…”
Section: Type I Ifn Therapy and Incident Thyroid Abnormalitiesmentioning
confidence: 99%